Fundamental of Entrepreneurship ENT300 Perfect Curve Fitness Centre / Muhamad Amirullah Sulaiman - Sulaiman, Muhamad Amirullah; Shamshor, Dayana Sazwani; Lawrance, Michellena; Remond, Cassielorina Lazz; Hipnee, Roslinda; Ahmar Saberi, Mohd Izham (2015)
Marketing is defined as the activities of a company associated with processes for creating, buying and selling a product or service. It includes advertising, selling and delivering products to people. Marketing must be carried out systematically and consecutively to encourage increase sales, which considered as the injection towards productivity of sales or services. It is one of the crucial elements in backbone of business. This element requires a systematic planning in order to ensure a product or service will be able to enter market and attract customers through alternatives lines of advertising and promotion. Many people believe that marketing is just about advertising or sales. However, marketing is everything a company does to acquire customers and maintain a relationship with them. The ultimate goal of marketing is to match a company's products and services to the people who need and want them, thereby ensure profitability. The entrepreneurs or the company's marketing manager must acknowledge the current demands and the condition of the market very well to improve their business performances. Therefore, to venture into a new business, it is important to analysis from marketing point of view along with a systematic marketing effort is essential to ensure target of sales and profitability are able to reached.